2016
DOI: 10.1007/s12291-016-0580-y
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of Differentiation 44 (CD44) Gene Variants: A Putative Cancer Stem Cell Marker in Risk Prediction of Bladder Cancer in North Indian Population

Abstract: CD44 is involved in cancer-cell growth, invasion, proliferation and metastasis and is also a causal factor for acquisition of resistance to apoptosis. Therefore we evaluated different SNPs of CD44 gene viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…In another Chinese study [22], Chen et al observed that rs187115 polymorphism was associated with the risk of cervical, lung, and liver cancer, but not with the risk of breast, gastric, colon or rectal cancer. In Indian populations, however, no significant association was found with gallbladder [23, 24] and bladder cancer patients [25]. In this present study, we found CD44 rs187115 polymorphism was associated with increased risk for CRC, which is different from the study by Chen et al [22].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In another Chinese study [22], Chen et al observed that rs187115 polymorphism was associated with the risk of cervical, lung, and liver cancer, but not with the risk of breast, gastric, colon or rectal cancer. In Indian populations, however, no significant association was found with gallbladder [23, 24] and bladder cancer patients [25]. In this present study, we found CD44 rs187115 polymorphism was associated with increased risk for CRC, which is different from the study by Chen et al [22].…”
Section: Discussioncontrasting
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) in CD44 gene may affect the protein expression, thereby influencing individuals’ susceptibility to cancer. In particular, a number of studies [1725] have explored the association between the CD44 rs187115 polymorphism and cancer risk, though their findings have been inconsistent. One Chinese study [22] found that CD44 rs187115 polymorphism was not associated with CRC risk in a southern Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…CC: ph = 0.085, I 2 = 46.057; TT vs . CC: ph = 0.288, I 2 = 1o.17) while removal of above studies together with Verma et al [ 47 ] was found to remove heterogeneity at allele level and in dominant model (T vs . C: ph = 0.576, I 2 = 0.000; CT+TT vs .…”
Section: Resultsmentioning
confidence: 99%
“…Bladder cancer was ranked the 12 th concerning malignancies worldwide in 2018 [ 1 ], and it also was the fourth most common cancer in the western world and the seventh worldwide in men [ 2 , 3 ], which has series medical and social concerns because of its frequent recurrence and poor prognosis [ 4 ]. Approximately 75% of newly diagnosed patients belongs to non-muscle-invasive bladder cancer (NMIBC).…”
Section: Introductionmentioning
confidence: 99%